2022
DOI: 10.3390/jcm11020380
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amino Acids May Improve Prediction Accuracy of Cerebral Vasospasm after Aneurysmal Subarachnoid Haemorrhage

Abstract: Aneurysmal subarachnoid haemorrhages (aSAH) account for 5% of strokes and continues to place a great burden on patients and their families. Cerebral vasospasm (CVS) is one of the main causes of death after aSAH, and is usually diagnosed between day 3 and 14 after bleeding. Its pathogenesis remains poorly understood. To verify whether plasma concentration of amino acids have prognostic value in predicting CVS, we analysed data from 35 patients after aSAH (median age 55 years, IQR 39–62; 20 females, 57.1%), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In a study involving 29 patients, amino acid levels were higher in the poor outcome group compared to the favorable outcome group, but the significance of the difference was very slight and was only observed in the early stage (0–3 days) [ 40 ]. In another study where plasma samples of aSAH patients were examined [ 41 ], no differences were found in the levels of amino acids between early and late samples, nor between the plasma amino acid levels of good and poor outcome groups; in fact, certain amino acid levels decreased in the plasma of aSAH patients compared to controls. Tuoho et al observed a hypermetabolic state in patients with ICH and aSAH undergoing surgery [ 42 ]; similar results were observed in another study [ 43 ], additionally demonstrating that increased amino acid infusion had no effect on amino acid exchange.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving 29 patients, amino acid levels were higher in the poor outcome group compared to the favorable outcome group, but the significance of the difference was very slight and was only observed in the early stage (0–3 days) [ 40 ]. In another study where plasma samples of aSAH patients were examined [ 41 ], no differences were found in the levels of amino acids between early and late samples, nor between the plasma amino acid levels of good and poor outcome groups; in fact, certain amino acid levels decreased in the plasma of aSAH patients compared to controls. Tuoho et al observed a hypermetabolic state in patients with ICH and aSAH undergoing surgery [ 42 ]; similar results were observed in another study [ 43 ], additionally demonstrating that increased amino acid infusion had no effect on amino acid exchange.…”
Section: Discussionmentioning
confidence: 99%
“…RDW can be expressed as a standard deviation (RDW-SD) or as a coe cient of variation (RDW-CV) [22]. Analysis conducted in 2022, showed that SAH patients with poor outcome, had had signi cantly greater RDW-CV on admission (13.9% vs 12.8%, p = 0.016) [23].…”
Section: Introductionmentioning
confidence: 99%
“…According to some clinicians, aSAH patients requiring prolonged mechanical ventilation have a poor prognosis 14 . Therefore, it is important to identify early prognostic predictors for patients with aSAH, as part of their management 15 . However, the long‐term clinical outcomes of aSAH patients requiring mechanical ventilation remain unpredictable, and no prognostic model has been developed.…”
Section: Introductionmentioning
confidence: 99%